Total and differential leucocyte counts in relation to incidence of stroke subtypes and mortality: a prospective cohort study - Elisabet Zia; Olle Melander; Harry Björkbacka; Bo Hedblad; Gunnar Engström (2012)
Elevated levels of total leucocyte as well as leucocyte subtypes have been associated with increased risk of atherosclerotic disease. Atherosclerosis is an important cause of cerebral infarction, whereas its significance in intracerebral haemorrhage (ICH) is less clear. A small number of prospective studies have revealed the relationship between leucocyte counts and incident stroke, in particular incidence of stroke subtypes. We evaluated the associations between total leucocyte count (TLC) as well as leucocyte subtypes and the incidence of and mortality caused by different stroke subtypes.Of 28 449 participants from the Malmö Diet and Cancer Study, 26 927 stroke-free subjects (mean age at screening, 58 ± 8 years) were included in a prospective cohort study. The screening period was between 1991 and 1996. Incidence of stroke, 1-year mortality and 1-month case-fatality rate (CFR) were assessed by linkage to local and national registers. Cox regression analysis was used to assess stroke risk and 1-year mortality, and 1-month CFR was assessed by logistic regression analysis.During a follow-up period of 13.6 ± 3.3 years, 1515 participants had a first-ever stroke (cerebral infarction, n = 1314; ICH, n = 201). After adjustments for other risk factors, TLC and neutrophil count were significantly associated with increased incidence of cerebral infarction (hazards ratio (HR), 1.4; 95% confidence interval (CI), 1.2-1.7 and 1.3; 95% CI, 1.1-1.5, respectively). There was an inverse association between elevated TLC and incident ICH (HR, 0.7; 95% CI, 0.4-0.99). No associations were found between leucocyte counts and mortality for either stroke subtype.The results suggest that the relationships with inflammation for ischaemic stroke and ICH are different.